Fundamentals of quantum optics and quantum information - Lambropoulos, Peter. (Springer, 2007)
The book that taught thousands of people about astrophotography has been completely revised and updated in this second edition. It covers everything you need to know to capture stunning images of deep-sky objects with a DSLR or CCD camera: The fundamental concepts of imaging and their impact on the final image; How to pick a telescope and camera; How to get set up and take the images; Where and when to find the best objects in the night sky; How to process images using PixInsight® and Adobe Photoshop®; Start-to-finish examples of image processing